Enhancing Social and Emotional Well-Being Through Drama Therapy: Evidence from Adolescents with Physical Disabilities - Namjoo, Farhad; Abdi, Mansour (Psychological Research in Individuals with Exceptional Needs, 2023)
The study aimed to evaluate the effectiveness of drama therapy on friendship quality and emotion regulation in adolescents with physical disabilities. A randomized controlled trial was conducted with 40 adolescents aged 13-18 years, randomly assigned to either an intervention group receiving drama therapy (n=20) or a control group (n=20). The intervention comprised ten 60-minute sessions over three months. Measures used included the Friendship Quality Scale (FQS) and the Emotion Regulation Questionnaire (ERQ), assessed at pre-intervention, post-intervention, and three-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests, with analyses performed in SPSS version 27. Significant improvements were observed in the intervention group compared to the control group. For friendship quality, the intervention group’s scores increased from a mean (M) of 55.12 (SD = 5.47) at pre-intervention to 68.25 (SD = 6.23) post-intervention and slightly decreased to 66.84 (SD = 6.01) at follow-up. Emotion regulation scores in the intervention group increased from 36.45 (SD = 4.12) at pre-intervention to 45.78 (SD = 4.96) post-intervention and slightly decreased to 44.67 (SD = 4.81) at follow-up. ANOVA results showed significant main effects for group and time (p < .001), with significant interactions between time and group for both variables (p < .001). Bonferroni post-hoc tests confirmed significant pre- to post-intervention and pre- to follow-up improvements in the intervention group (p < .001). Drama therapy significantly enhances friendship quality and emotion regulation in adolescents with physical disabilities, with effects sustained at a three-month follow-up. These findings support the incorporation of drama therapy in therapeutic programs for this population to address their unique psychosocial challenges.